Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A R O S (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A. R. O. S. (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.065510.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem

Rhythmic growth rings of wood and their relationship with the foliage in oak seedlings grown in a favourable environment - MANSOUR, A.; de FAŸ, E. (Annals of botany, 1998)
{{The anatomy of wood was studied in Quercus robur L. and Quercus suber L. seedlings exhibiting 3±8 units of extension, each with a tier of photosynthesizing leaves in their upper parts, generated as the result of rhythmic shoot growth under favourable conditions. At all the axis levels examined (i.e. the base of each of the diﬀerent units of extension, four other equidistant levels within the ®rst unit of extension and the upper part of the taproot), the wood displayed rings when treated with Wiesner reagents. This indicated cinnamaldehyde groups present in lignins. No rings appeared when the Mau$le reaction was used for speci®c detection of syringyl subunits in lignins. A trend towards a periodical arrangement of xylem parenchyma bands was also found when sections were treated with I # }KI. The number of rings coincided with the number of leaf tiers above the level of measurement, and did not vary inside the ®rst unit of extension. Thus, the rings are called rhythmic growth rings. In sections of the ®rst and the second units of extension, and in the taproot, the area and width of a given rhythmic growth ring were highly correlated with the total area of leaves present above the level of measurement at the presumed time of growth ring formation. Moreover, stem diameter at the base of the units of extension was highly correlated with the leaf area above. These results indicate that diﬀerentiation of xylem, particularly its ligni®cation, varies rhythmically in oak seedlings. They imply that wood production is linked to the photosynthesizing and}or transpiring area of the plant. Thus, during a growth cycle of Q. robur and Q. suber seedlings, there appears to be integration of the primary metabolic activities with the laying down of rhythmic growth rings
Keywords: allometric relationship; juvenile wood; leaf area; lignification; oak seedling; periodic structure; quercus robur l; Quercus Suber L; rhythmic growth ring; unit of extension

Rhythmic growth rings of wood and their relationship with the foliage in oak seedlings grown in a favourable environment - MANSOUR, A; de FAŸ, E (Annals of botany, 1998)
{{The anatomy of wood was studied in Quercus robur L. and Quercus suber L. seedlings exhibiting 3±8 units of extension, each with a tier of photosynthesizing leaves in their upper parts, generated as the result of rhythmic shoot growth under favourable conditions. At all the axis levels examined (i.e. the base of each of the diﬀerent units of extension, four other equidistant levels within the ®rst unit of extension and the upper part of the taproot), the wood displayed rings when treated with Wiesner reagents. This indicated cinnamaldehyde groups present in lignins. No rings appeared when the Mau$le reaction was used for speci®c detection of syringyl subunits in lignins. A trend towards a periodical arrangement of xylem parenchyma bands was also found when sections were treated with I # }KI. The number of rings coincided with the number of leaf tiers above the level of measurement, and did not vary inside the ®rst unit of extension. Thus, the rings are called rhythmic growth rings. In sections of the ®rst and the second units of extension, and in the taproot, the area and width of a given rhythmic growth ring were highly correlated with the total area of leaves present above the level of measurement at the presumed time of growth ring formation. Moreover, stem diameter at the base of the units of extension was highly correlated with the leaf area above. These results indicate that diﬀerentiation of xylem, particularly its ligni®cation, varies rhythmically in oak seedlings. They imply that wood production is linked to the photosynthesizing and}or transpiring area of the plant. Thus, during a growth cycle of Q. robur and Q. suber seedlings, there appears to be integration of the primary metabolic activities with the laying down of rhythmic growth rings
Keywords: allometric relationship; juvenile wood; leaf area; lignification; oak seedling; periodic structure; quercus robur l; Quercus Suber L; rhythmic growth ring; unit of extension